Rectal Prolapse in a Child: An Unusual Presentation of Clostridium difficile–Associated Pseudomembranous Colitis - Shu-Ching Huang; Yao-Jong Yang; Chung-Ta Lee (Pediatrics and Neonatology, 2011)
Pseudomembranous colitis after short-course antibiotics is rare in children. We report a 14-month-old girl who presented with rectal prolapse complicated with Clostridium difficile–associated pseudomembranous colitis after a 4-day course of oral cefuroxime for treatment of acute otitis media. Abdominal sonogram showed a pelvic mass, and computed tomography revealed thickened wall of the rectum. Sigmoidoscopy demonstrated discrete yellowish plaques adherent to an edematous mucosa. Stool cultures for C difficile were positive and C difficile toxins A and B were detected in her stool. Histological examination of colonic biopsy showed superficial erosion of the mucosa and the adherent pseudomembranes. She achieved a full recovery after discontinuing cefuroxime. Our case implied that C difficile infection should be considered in children presenting with rectal prolapse, especially when they are taking or have recently received antibiotic therapy. Supportive therapy and discontinuation of antibiotics are generally sufficient for patients with C difficile–associated pseudomembranous colitis who present with mild diarrheal illness.